2020
DOI: 10.3390/ma13040934
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Alginate Nanofibers Toward Various Applications: A Review

Abstract: Alginate has been a material of choice for a spectrum of applications, ranging from metal adsorption to wound dressing. Electrospinning has added a new dimension to polymeric materials, including alginate, which can be processed to their nanosize levels in order to afford unique nanostructured materials with fascinating properties. The resulting nanostructured materials often feature high porosity, stability, permeability, and a large surface-to-volume ratio. In the present review, recent trends on electrospun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 88 publications
(193 reference statements)
0
55
0
Order By: Relevance
“…Notably, high conductivity can prevent fiber formation by causing strong repulsive forces between polymer chains that prevent entanglements during electrospinning. [34][35][36]61,71 One of the reasons that a linear copolymer, like PEO, is used to electrospin alginate is because the PEO chains wrap around the rigid alginate chains to interrupt interactions between alginate and sodium ions lowering the conductivity of the solution. 36 We observed this effect, too.…”
Section: Effect Of Conductivity On Alginate-based Nanofibersmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, high conductivity can prevent fiber formation by causing strong repulsive forces between polymer chains that prevent entanglements during electrospinning. [34][35][36]61,71 One of the reasons that a linear copolymer, like PEO, is used to electrospin alginate is because the PEO chains wrap around the rigid alginate chains to interrupt interactions between alginate and sodium ions lowering the conductivity of the solution. 36 We observed this effect, too.…”
Section: Effect Of Conductivity On Alginate-based Nanofibersmentioning
confidence: 99%
“…PEO chains can interfere with the interaction between sodium ions and alginate chains which are the major contributors to the conductivity in this system. [34][35][36]61,71 Therefore, decreasing the concentration of alginate while increasing the PEO concentration will decrease the solution conductivity. When the ratio of SA to PEO was changed from 2.5 to 1.5, the resulting conductivity of the 2.5/1.5/3 wt% SA/PEO/PS80 solution with 10 8 CFU mL −1 of E. coli was 4.74 ± 0.08 mS cm −1 , which was significantly lower than all other bacteria loaded solutions.…”
Section: Papermentioning
confidence: 99%
“…There is a lot of research investigating antimicrobial biomedical application [22][23][24][25][26][27]. Many researchers have studied the electro-spinning method for biomedical application [28][29][30][31][32][33][34][35][36][37].…”
Section: Electro-spinning For Biomedical Applicationsmentioning
confidence: 99%
“…Thus, other substances, e.g., cinnamaldehyde (CA) [ 48 ], aqueous salt solutions, e.g., CaCl 2 [ 51 ], citric acid [ 52 ], and agents such as genipin (GP) or N-3-dimethylaminopropyl-N’-ethylcarbodiimide hydrochloride (EDC), are used [ 46 , 53 ]. A great comparison of the impact of various, widely used crosslinkers on the process of denaturation of the collagen fibers can be found in the paper by Luo et al [ 50 ] As the authors have reported, while all evaluated crosslinkers (GP, GTA, and EDC-N-hydroxysuccinimide (NHS)) were effective in inhibiting the materials’ solubility over 2 months of incubation (while the un-crosslinked material had completely dissolved), GTA reduced the material’s cytocompatibility, while GP or EDC both were less effective in maintaining intact fibrous morphology ( Figure 3 ) [ 50 ], leading to the conclusion that there is no universal chemical crosslinker that would combine excellent biocompatibility with an ability to maintain an intact fibrous morphology.…”
Section: The Crosslinking Strategiesmentioning
confidence: 99%